TANGGUNG JAWAB NOTARIS ATAS KEAMANAN MINUTA AKTA ELEKTRONIK DALAM ERA DIGITALISASI - Nabilla, Tasya; Farma Rahayu, Mella Ismelina (Kertha Semaya : Journal Ilmu Hukum, 2025)
The development of digital technology has driven a significant transformation in notarial practice, especially through the implementation of the cyber notary concept that changes the process of creating, storing, and validating minutes of deeds from physical to electronic format. Digitalization of minutes of deeds offers better efficiency, speed, and ease of access, supported by certified electronic signature technology and a secure cloud-based storage system. However, the implementation of electronic minute storage faces major challenges related to regulations that are not yet harmonized between the Notary Law and the Electronic Information and Transactions Law (UU ITE), as well as the absence of clear technical standards regarding data security and protection. This unclear regulation poses legal risks, such as doubts about the validity of electronic documents as evidence in court, as well as the potential for loss, damage, or data leakage that can harm the parties. Notaries as public officials have comprehensive legal responsibilities to maintain the authenticity, confidentiality, and integrity of electronic minutes, with the obligation to protect personal data in accordance with the Personal Data Protection Law. The notary's liability includes civil, administrative, and criminal aspects if there is a violation or negligence in the management of electronic minutes. Therefore, harmonization of regulations, development of technical standards for information security, and increasing the capacity and awareness of notaries in the use of digital technology are essential. These steps are important to ensure that the storage of electronic minutes is not only efficient and practical, but also has the same legal force as physical documents, so that it can provide legal certainty and maximum protection for the parties and maintain the integrity and public trust in the notary profession in the digital era.